IL-10−/− Enhances DCs Immunity Against Chlamydia psittaci Infection via OX40L/NLRP3 and IDO/Treg Pathways - Li, Qiang; Li, Xiaohui; Quan, Hongkun; Wang, Yihui; Qu, Guanggang; Shen, Zhiqiang; He, Cheng (Frontiers in Immunology, 2021)
Chlamydia psittaci (C. psittaci) is a zoonotic agent that impacts both the poultry industry and human beings. Interleukin 10 (IL-10) regulates chlamydial infection as an anti-inflammatory factor and dendritic cells (DCs) are the powerful antigen-presenting cell type in the host that induce the primary immune response. However, the regulation mechanisms of IL-10 and DCs during C. psittaci infection remains elusive. To investigate the regulation in vivo and in vitro, IL-10−/− mice, conditional DC depletion mice (zinc finger dendritic cell-diphtheria toxin receptor [zDC-DTR]), and double-deficient mice (IL-10−/−/zDCDTR/DTR) were intranasally infected with C. psittaci. Subsequently, more than 90% of IL-10−/− mice, 85% of IL-10 inhibitor (ammonium trichloro (dioxoethylene-o,o') tellurate [AS101])-treated mice, 70% of wild-type mice, and 60% of double-deficient mice survived, whereas all zDC-DTR mice died. A higher lymphocyte proliferation index was found in the AS101-treated mice and IL-10−/− mice. Moreover, severe lesions and high bacterial loads were detected in the zDC-DTR mice compared with double-deficient mice. In vitro, OX40-OX40 ligand (OX40-OX40L) activation and proliferation of CD4+T cells were increased, whereas the expression of indoleamine 2, 3-dioxygenase and regulatory T cells were significantly reduced after co-culture of IL-10−/− DCs/ CD4+ T cells with C. psittaci. Additionally, activation of the NLR family pyrin domain-containing 3 (NLRP3) inflammasome was increased to facilitate the apoptosis of DCs, leading to rapid clearance of C. psittaci. Our study indicated that IL-10−/− was able to upregulate the function of deficient DCs by activating OX40-OX40L, T cells, and the NLPR3 inflammasome, and inhibiting indoleamine 2, 3-dioxygenase and regulatory T cells. These effects led to a high rate of survival in mice and clearance of C. psittaci. Further our research highlights the mechanism of IL-10 interaction with DCs, OX40-OX40L, and the NLPR3 inflammasome – three potential targets against C. psittaci infection.